Parental involvement and school engagement reduce adolescent aggressive behaviors: a three wave cross-lagged model - Wang, Zhen; Chen, Yuanyuan; Su, Yunsheng; Song, Yan; Tao, Zhiyuan (Frontiers in Public Health, 2025)
ObjectiveAggressive behaviors can have severe negative consequences on the psychological and behavioral development of adolescents. This study incorporated parental involvement, school engagement, and aggressive behaviors to construct a cross-lagged model to explore the mediating mechanism of school engagement between parental involvement and aggressive behaviors.MethodsA total of 1,835 adolescents (55.9% boys; Meanage = 12.34) completed three rounds of offline survey questionnaires (T1–T3). Descriptive statistics were performed using SPSS 26, followed by the construction of a cross-lagged model using Mplus 8.4.ResultsThe structural equation model showed: (1) T2 school engagement positively mediated the relationship between T1 parental involvement and T3 aggressive behaviors; (2) A bidirectional relationship was established, where T2 school engagement also mediated the relationship between T1 aggressive behaviors and T3 parental involvement.ConclusionThis study reveals the detailed mechanisms of how parental and school engagement influence adolescent aggressive behaviors, emphasizing the importance of the interaction between individuals and their environment in the mechanisms of aggressive behaviors.